Hopping conductivity in GaSe monocrystals at low temperatures - Pashayev, A.M.; Gadjiyev, A.R.; Tagiyev, T.B.; Abbasova, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The paper represents results of investigation in the wide temperature interval (4.2…300) K of hopping conductivity in GaSe single crystals doped by cadmium impurities (0.01 and 0.1 atomic percent) during crystal growing. Specific resistance of GaSe doped by cadmium at room temperature is equal to 31 and 250.0 ohm•cm, concentration of impurities is 10¹⁵ and 2.0×10¹⁶ cm⁻³, mobilities are equal to 25.0 and 12.0 cm2/V•sec, respectively. It is ascertained that specific resistance weakly depends on temperature at (5…33)K, activation energy of this conductivity is 1.2×10⁻³ eV, and it is determined by hopping mechanism of charge transfer. At temperatures (33…100)K, activation energy of conductivity is 7.8×10⁻² eV, and it is connected with hole transfer in empty band.